Training needs analysis on Indonesian construction workers competency in Malaysia - Ismail, Fadillah; Abdul Kadir, Zulida; Jaes, Lutfan (Science Publishing Corporation, 2018)
The growth of construction industry in Malaysia is stimulated by various mega infrastructure projects. Due to this, the competent construction workers become the catalyst in realizing the goals. Using mixed method approach in explanatory research, this study aimed to analyze the training needs based on 300 Indonesian construction workers’ competency. Findings showed that there are significant differences between knowledge and skills possessed by the Indonesian workers, based on two types of training; theory and practical. However, the training on skills is considered critical as it is a need for the Indonesian workers to fulfil the job requirements in Malaysia.